Box-Behnken design optimization of sulfate reduction from natural water by electrocoagulation process. (1st February 2023) - Chibani, Amel; Ncib, Sana; Barhoumi, Afef; Bouguerra, Wided; Elaloui, Elimame
Abstract: The purpose of this work is to investigate sulfate removal from aqueous solutions by electrocoagulation (EC). The influence of electrolysis time, initial pH, and current density was carried out. The interaction of the several effects on removal efficiency was also studied. The Box-Behnken experimental design (BBD) in Response Surface Methodology (RSM) was applied in the development of statistical analysis, modeling, and interpretation of the resultant treatment data of sulfate removal by EC. The optimum conditions for highest removal ratio of sulfate from aqueous solution were: current density of 10 mA/cm 2, initial pH equal 5 and electrolysis time of 60 min. Sulfate removal efficiency reach a maximum value of 98.76% and the predicted value is 100%. According to ANOVA results, the correlation coefficient (R 2 ) value of 98% proved that experimental data and model predictions agreed well. The R 2 adj and R 2 pred were also in a reasonable agreement (98% and 95% respectively). The mathematical model that describes the EC process was determined and proved that all variable had linear and quadratic significant effect on sulfate removal efficiency. The optimum conditions founded using BBD conducted to 60 and 90% of sulfate removal respectively from seawater and brackish water. Graphical Abstract: UF0001